12.2: Flame‐Resistant and Heat‐Resistant Lithium‐Ion Battery Used to Operate Heat‐Resistant OLED. Issue 1 (June 2015) - Ishikawa, Jun; Oguni, Teppei; Narita, Kazuhei; Hitotsuyanagi, Aya; Yamakaji, Masaki; Momo, Jumpei; Hirohashi, Takuya; Yoshitani, Yusuke; Nowatari, Hiromi; Takahashi, Tatsuyoshi; Suzuki, Tsunenori; Seo, Satoshi; et al.
Abstract : A flame‐ and heat‐resistant lithium‐ion battery (LIB) has been developed using ionic liquid electrolyte. This battery can be stably discharged at 100°C as well as at 0°C. A heat‐resistant organic light‐emitting diode (OLED) using this battery as a power source has been stably operated at temperatures of 100°C and 0°C.